MR and CT based treatment planning for mTHPC mediated interstitial photodynamic therapy of head and neck cancer: Description of the method. Issue 8 (4th September 2013) - Karakullukcu, Baris; van Veen, Robert L.P.; Aans, Jan Bonne; Hamming‐Vrieze, Olga; Navran, Arash; Teertstra, H. Jelle; van den Boom, Ferrie; Niatsetski, Yuri; Sterenborg, H.J.C.M.; Tan, I. Bing
Abstract Background and Objective Interstitial photodynamic therapy is a potentially important tool in the management of voluminous or deep‐seated recurrent head and neck cancers. Study Design/Methods The described treatment algorithm in this manuscript consists of the treatment simulation, implantation of light sources, verification, modification of the treatment plan if necessary, and illumination. The tumor is delineated on imaging sections (CT, MRI, and/or PET/CT) and the treatment is simulated by virtually introducing light sources to the tumor volume on specially modified brachytherapy software. This enables us to determine if the treatment is technically feasible, and information about approximate number and location of light sources necessary. Following implantation of catheters in which the light sources will be introduced, CT or MR scan is performed to verify the actual location of the implanted catheters. The verification‐CT is imported to the software and co‐registered with pre‐treatment images to observe the deviations from the simulation. The simulation is run again with the actual position of the light sources to determine if any additional light sources are necessary and adaptation of the source length in order to cover the tumor volume (modification). Thereafter the tumor is illuminated. Results This method has the potential to help with identifying iPDT feasible patients by simulating before the actual treatment. The suboptimal placement of light sources can be identified and corrected. The simulations were documented and saved for subsequent evaluation of the technique. Conclusion The proposed technique can help standardize and document iPDT. Lasers Surg. Med. 45:517–523, 2013. © 2013 Wiley Periodicals, Inc.